PENGARUH PENGUASAAN KOSAKATA BAHASA ARAB TERHADAP KEMAMPUAN BERBAHASA ARAB SISWA PONDOK DARUL ARQAM MUHAMMADIYAH PUNNIA PINRANG - Hunaidu Hunaidu; Mahlani Sabae (Universitas Muhammadiyah Makassar, 2019)
This study aims to: 1) determine the Arabic language skills of students at Darul Arqam Muhammdiyah Punnia Pinrang students. 2) knowing the Arabic vocabulary mastery of students at Darul Arqam Muhammadiyah Punnia Pinrang students. 3) determine the effect of mastering Arabic vocabulary on Arabic language skills of students of Darul Arqam Muhammadiyah Punnia Pinrang. This type of research is a qualitative descriptive study, with data collection methods carried out by observation, interviews, questionnaires and documentation. The results of this study explain that 1) the Arabic language skills of Pondok Darul Arqam Muhammadiyah Punnia students can be said to be quite good because the teacher who teaches is already quite an expert in the Arabic language and learning methods in conveying subject matter as needed. 2) mastery of students 'Arabic vocabulary is not optimal because there are no indicators related to mastery of students' vocabularies that develop optimally which includes mastery of active-productive (speaking-writing) and passive-receptive (reading-listening) vocabulary. 3) the results of the questionnaire showed that the mastery of Arabic vocabulary affected students' Arabic language ability and increased, and of course had a different method from the previous one so that the learning process did not cause boredom.Keywords: Vocabulary, Improvement, Ability